Factors Associated with Suicidal Ideation among Junior High School Students in Mueang District, Nakhon Ratchasima Province - Prachumchalad, Suphakarn; Sukadaecha, Rungrat; Phonsongkram, Arriya; Pongkhamsing, Tairat; krueasaeng, Chonthicha; kakunmalee, Pitchayapa; Teamthong, Wannisa; Saosiri, Supaporn (Princess of Naradhiwas University Journal, 2025)
The purpose of this predictive regression analysis study was to investigate the factors associated with suicidal ideation in junior high school students. A multi-stage random sampling was used to recruit samples of 280 junior high school students in Mueang district, Nakhon Ratchasima province. The following research tools were used: 1) a questionnaire about stressful life events; 2) a measure of adolescents’ coping strategies; and 3) an assessment of suicide ideation. The results of reliability indexes of these instruments were 0.91, 0.71, and 086, respectively. Data were analyzed by using frequency, percentage, average, standard deviation, range, and multiple regression analysis. The findings showed that: 1) The three most stressful events in their lives were students’ problems with their study course, study limitations, and friends, with scores of 90.00, 85.40, and 83.90, respectively; 2)The three coping strategies that students used the most were self-competency, other support resources, and problem avoidance (81.10, 64.30, and 44.60, respectively); 3) students’ suicidal ideation was low, high, and very high (79.30, 12.10, and 8.60, respectively); 4) There were five factors linked to suicidal ideation in students: coping strategies by avoiding problems, coping strategies by using other resources for support, stressful life events involving study course problems, problems with teachers, and problems with lovers (β =.291, -.279, .131, .126, and .126, respectively) .Suicidal ideation among students was predicted by these characteristics in 29.10% (R2=.291, p<.05). The results can be used to reduce suicide ideation in students by reducing stressful events and encouraging students to use appropriate coping strategies.